Casting techniques of equine hand and foot synovial cavities for the development of teaching models - Velásquez, José Miguel; Tamayo-Arango, Lynda; Santos-Silva, Thamires; Miglino, Maria Angelica (Frontiers in Veterinary Science, 2025)
Horse joints are common sites of injury, orthopedic issues, and surgical and clinical interventions. For this reason, a thorough understanding of joint anatomy, including the boundaries of their recesses and their relationships with other structures of the locomotor apparatus, is essential. This study aimed to develop cast anatomical models of the synovial structures of the equine hand and foot, compare different casting materials and visualization methods, and identify the most suitable technique for enhancing the understanding of equine limb arthrology. Additionally, an anatomical description of the synovial structures was performed to evaluate whether all relevant structures were adequately visualized using these techniques. We employed a combination of techniques, using various casting materials (methyl methacrylate, flexible epoxy resin, Smooth Cast® 300, and latex), biological maceration using dermestid beetles (Coleoptera: Dermestidae), and dissection to visualize the cavities of the carpus, tarsus, metacarpophalangeal, and interphalangeal joint. Also, the tendon sheaths of the digital flexors, extensor carpi radialis, and lateral digital flexor muscles were cast, and the podotrochlear and calcaneal subtendinous bursa were also injected. Three casting models of the metacarpophalangeal and interphalangeal joints underwent natural maceration using dermestid beetles, while the remaining joints and structures were dissected. All joints, bursa, and tendon sheaths were successfully filled with varying amounts of polymers. We concluded that joint casting is an effective and straightforward technique for producing models that enhance the understanding of the capacity and boundaries of these cavities, thereby facilitating the teaching of veterinary arthrology. We recommend methyl methacrylate as the most suitable casting material due to its ability to fill smaller cavities effectively and latex as a cost-effective option that yields good results in larger cavities. We advocate for the use of biological maceration because it avoids the use of chemicals that generate waste and toxic vapors. Future research should focus on evaluating the effectiveness of these models in enhancing the learning experience for students.